2010
DOI: 10.1111/j.1469-8749.2009.03352.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating attention deficits in children with fetal alcohol spectrum disorder or attention‐deficit–hyperactivity disorder

Abstract: CPT Continuous Performance Task FASD Fetal alcohol spectrum disorder AIM The attention and inhibition problems found in children with attention-deficit-hyperactivity disorder (ADHD) are also common in children with fetal alcohol spectrum disorders (FASDs). Attempts to distinguish ADHD from FASDs in terms of these deficits are rare and were pursued in this study.METHOD A total of 116 children (47 with ADHD, 31 males, 16 females; 30 with FASDs, 17 males, 13 females; and 39 comparison children, 20 males, 19 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 32 publications
(40 reference statements)
3
47
2
1
Order By: Relevance
“…Although the CPT has marginal utility in detecting behavioral characteristics of ADHD, 34 the vast majority of studies have found the CPT to be an important and useful tool for not only demonstrating attention deficits in specific childhood disorders such as asthma 35 and fetal alcohol syndrome, 36 but also as a psychometric instrument for the detection of neural processing deficits in children with ADHD. Our current understanding suggests that in the majority of these children, seizures will remit in adolescence and they will enter adulthood seizure-free off medications.…”
Section: Statistical Analysis Baseline Neurocognitive Test Results Amentioning
confidence: 99%
“…Although the CPT has marginal utility in detecting behavioral characteristics of ADHD, 34 the vast majority of studies have found the CPT to be an important and useful tool for not only demonstrating attention deficits in specific childhood disorders such as asthma 35 and fetal alcohol syndrome, 36 but also as a psychometric instrument for the detection of neural processing deficits in children with ADHD. Our current understanding suggests that in the majority of these children, seizures will remit in adolescence and they will enter adulthood seizure-free off medications.…”
Section: Statistical Analysis Baseline Neurocognitive Test Results Amentioning
confidence: 99%
“…Behaviors associated with the effects of PAE appear similar to behaviors observed in children with attention deficit hyperactivity disorder (ADHD) [53][54][55][56]. However, there are differences between the two disorders [55,56].…”
Section: Fasd and Problematic Behaviormentioning
confidence: 85%
“…However, there are differences between the two disorders [55,56]. Many children affected by PAE exhibit inefficient speed of processing, problems shifting attention, and difficulties modulating arousal level when both under-and overstimulated [56].…”
Section: Fasd and Problematic Behaviormentioning
confidence: 99%
See 2 more Smart Citations